RELATIONSHIP BETWEEN AGE AND COMMON BILE DUCT DIAMETER IN ADULTS: ULTRASONOGRAPHIC STUDY: Pharmaceutical Sciences-Medicine - NALAINI, FARHAD; GHARIB SALEHI, MOHAMMAD; FARSHCHIAN , NAZANIN (International Journal of Life Science and Pharma Research, 2017)
There is controversy regarding whether with increasing age, the common bile duct (CBD) diameter on ultrasound examination increases or not. We decided to assess relationship between age and CBD diameter in healthy individuals. A total of 190 patients underwent trans-abdominal ultrasound. In supine position, first a brief evaluation of the liver, pancreas, gallbladder, and bile ducts was done. Then, on sagittal plan, when the CBD was visualized in longitudinal axis, during deep inspiration, in its proximal portion the anteroposterior distance from inner borders was measured. There was a statistically significant correlation between age and the CBD diameter (P< 0.001, r= 0.47). When the analyses were done separately for genders, these values were also found to be significant as r= 0.5 (P< 0.001) in males and r= 0.542 (P< 0.001) in females. There was a significant relationship between age and the CBD diameter. In normal individuals, the normal size of the CBD increases as they get older.